2006
DOI: 10.1128/jvi.80.4.1798-1806.2006
|View full text |Cite
|
Sign up to set email alerts
|

Importin-β Family Members Mediate Alpharetrovirus Gag Nuclear Entry via Interactions with Matrix and Nucleocapsid

Abstract: The retroviral Gag polyprotein orchestrates the assembly and release of virus particles from infected cells. We previously reported that nuclear transport of the Rous sarcoma virus (RSV) Gag protein is intrinsic to the virus assembly pathway. To identify cis-and trans-acting factors governing nucleocytoplasmic trafficking, we developed novel vectors to express regions of Gag in Saccharomyces cerevisiae. The localization of Gag proteins was examined in the wild type and in mutant strains deficient in members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 57 publications
5
86
0
Order By: Relevance
“…Parent and colleagues have shown in a series of studies that Rous sarcoma virus (RSV) Gag shuttles (6,17,20,(45)(46)(47), and experiments with RSV Gag mutants that do not undergo nuclear cycling provided evidence that this is needed for efficient gRNA encapsidation (17,45). RSV Gag nuclear import is mediated by NLSs in MA and NC (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parent and colleagues have shown in a series of studies that Rous sarcoma virus (RSV) Gag shuttles (6,17,20,(45)(46)(47), and experiments with RSV Gag mutants that do not undergo nuclear cycling provided evidence that this is needed for efficient gRNA encapsidation (17,45). RSV Gag nuclear import is mediated by NLSs in MA and NC (45).…”
Section: Discussionmentioning
confidence: 99%
“…(K to Q) Subcellular localization of FIV MA-CFP, CA-CFP, and NCp2-CFP. Transfected HeLa cells were treated or not with LMB for 3 h. The nuclear/total MFI (Q) was determined as described above for panel J for 158 cells (6,17,25,23,15,15,21,16,11, and 9 cells for columns from left to right, respectively). Images are representative of at least three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies identified the nuclear import receptors for the isolated MA and NC domains in yeast (13). To test whether the mammalian homologues of these karyopherins were associated with MA and NC in avian cells, the natural host for RSV, MA-GFP and YFP-NC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Genetic analysis using Saccharomyces cerevisiae revealed that nuclear import of NC depends on the importin-α/β (imp-α/β) pathway, whereas Kap120p and Mtr10p [transportin-SR and importin-11 (imp-11), respectively, in higher eukaryotes] are import receptors for MA (13). Toxicity of the Gag protein in yeast prevented determination of whether it interacts with the same karyopherins as the isolated MA and NC domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation